Evaluation of groundwater quality and its suitability for drinking purposes in semi-arid region of Southern India: an application of GIS. Issue 25 (13th December 2022) - Adimalla, Narsimha; Manne, Ravi; Zhang, Yunhui; Xu, Panpan; Qian, Hui
Abstract: In the present study, the quality of groundwater for drinking purposes was evaluated. The following parameters were analyzed using American Public Health Association standard method: pH, total hardness (TH), total dissolved solids (TDS), electrical conductivity (EC), bicarbonate (HCO3 − ), chloride (Cl − ), sulphate (SO4 2− ), fluoride (F − ), calcium (Ca 2+ ), magnesium (Mg 2+ ), sodium (Na + ) and potassium (K + ). These values were compared with limits recommended by the World Health Organization (WHO) and the Bureau of Indian Standards (BIS) for drinking purposes. The cation and anion dominance of the study region groundwater samples were Na + > Ca 2+ > Mg 2+ > K + and HCO3 − > Cl − > SO4 2− > F −, respectively. Bicarbonate was the dominant anion and Na + was identified as the dominant cation in the groundwater of the study region. The Na + and Cl − concentration of 43% and 37% of groundwater samples were found to be more than the acceptable limit of WHO in the study region. Most of the groundwater samples in the study region were categorized as a very hard category. The groundwater was highly affected by the fluoride and about 60% of groundwater samples were unfit for drinking purposes in the study region.